Tough bonding method of trehalose modified hydrogel and dehydration induction strengthening method

By introducing trehalose into the hydrogel and using dehydration-induced strengthening methods, the problems of poor adhesive performance and insufficient stability of the hydrogel were solved, and its bonding strength and environmental adaptability were significantly improved.

CN119331521AActive Publication Date: 2025-01-21ZHEJIANG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411869058.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-01-21
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing hydrogels have poor bonding performance and insufficient stability in long-term applications, especially when used in high temperature and low humidity environments, their reliability is greatly limited.

Method used

By introducing trehalose and taking advantage of its strong hydrogen bonding effect, the bonding strength of hydrogels with various materials can be significantly improved, and the stability of hydrogels in extreme environments can be improved through dehydration-induced strengthening methods.

Benefits of technology

Significantly improves the bonding strength and environmental stability of the hydrogel, ensuring that it maintains long-term and reliable bonding effects in complex biological environments and extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331521A_ABST
    Figure CN119331521A_ABST
Patent Text Reader

Abstract

The invention discloses a trehalose modified hydrogel tough bonding method and a dehydration induction strengthening method. The adhesive property of the traditional hydrogel is often reduced in a water loss or extreme environment, so that the application of the traditional hydrogel in biomedicine and electronic equipment is limited. According to the invention, trehalose is introduced, and a polar group of trehalose is utilized to induce formation of a strong hydrogen bond, so that the bonding strength between the hydrogel and different material interfaces is remarkably enhanced, and tough bonding of the hydrogel in a water loss or extreme environment is realized. Besides, by controlling the dehydration process of the hydrogel, free water in the hydrogel is gradually reduced, and the proportion of bound water is increased, so that a network structure with stronger interaction is formed, and the bonding strength is further improved. The high-strength adhesive is suitable for high-strength bonding requirements in a harsh environment, can improve the long-term use reliability and environmental adaptability of devices such as hydrogel supercapacitors and the like, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogel materials, and in particular to a trehalose-modified hydrogel strong-tough bonding method and a dehydration-induced strengthening method. Background Art

[0002] Hydrogels have been widely used in many fields, including biomedicine (such as drug delivery, tissue engineering, wound dressings, etc.), electronic devices, flexible sensors and soft robots, due to their unique softness, extremely high water content and responsiveness to environmental stimuli. Especially in biomedical engineering, hydrogel bonding technology, as a representative of soft and wet material bonding, has become an important research direction in this field. The high hydration and hydrophilicity of hydrogels give them good interfacial bonding ability with biological tissues, cells or other biological materials, making them an ideal choice for applications such as tissue repair, drug delivery, neural prostheses and bioelectronics. For example, in tissue repair and drug delivery, hydrogels can not only serve as stable drug carriers to ensure the continuous release of drugs or bioactive factors, but also can intelligently control the drug release rate according to changes in the biological environment, thereby achieving more precise treatment. In addition, the responsiveness of hydrogels enables them to adapt to the needs of different biological environments, enhancing their application potential in personalized treatment, precision medicine and chronic disease treatment, especially in dynamically changing physiological environments, which can provide long-term treatment support.

[0003] As a three-dimensional cross-linked polymer network, hydrogel is rich in hydrophilic groups, has excellent hydration ability, unique gel structure and high customizability. These characteristics enable it to play an important role as an interactive bridge between materials such as metals, silicon, glass, ceramics, rubber, etc., and become an indispensable material in emerging fields such as brain-computer interfaces, neural prostheses, medical implants and wearable devices. Hydrogels can not only effectively bond different materials, but also provide excellent interfaces with biological tissues, ensuring efficient information transmission and compatibility between bioelectronic devices and organisms. For example, in brain-computer interfaces and neural prostheses, the flexibility and biocompatibility of hydrogels enable them to be closely integrated with human tissues to achieve long-term and stable biological signal transmission. With the rapid development of these high-tech fields, the interfacial bonding properties of hydrogels have become a key factor affecting their application functions and reliability. Therefore, improving the bonding strength, stability and durability of hydrogels in complex biological environments has become one of the core goals of current research. Especially in the fields of medical, electronic and intelligent devices, the reliability and durability of hydrogel bonding directly determine its application prospects.

[0004] However, hydrogels still face some challenges that need to be addressed in long-term applications. Due to their high water content, traditional hydrogels are prone to water loss during use, which leads to a significant decrease in bonding performance, especially when used in high temperature and low humidity environments (such as electronic equipment bonding). Its reliability is greatly limited. In addition, hydrogels are not stable enough in extreme environments, especially in harsh environments such as aerospace, deep-sea exploration, and extreme cold. Hydrogels need to be able to withstand extreme temperature and humidity changes to ensure their reliability under these extreme conditions. Summary of the invention

[0005] The purpose of the present invention is to solve the defects of poor adhesion and insufficient stability of hydrogels in the prior art, and to provide a trehalose-modified hydrogel tough bonding method and a dehydration-induced strengthening method. The present invention aims to significantly improve the bonding strength of hydrogels with various materials through the strong hydrogen bonding effect induced by trehalose, while giving them excellent environmental adaptability. Trehalose, as a natural sugar compound, has good biocompatibility, low toxicity and biodegradability. In the hydrogel system, it can not only enhance the bonding performance, but also effectively improve the stability of the hydrogel in extreme environments.

[0006] The technical solutions specifically adopted in the present invention are as follows:

[0007] In a first aspect, the present invention provides a method for strong bonding of trehalose-modified hydrogels, the steps of which are as follows:

[0008] S1, dissolving 5-25 parts by weight of trehalose (T) and 7 parts by weight of acrylamide (AAm) monomer in water to form 50 parts by weight of a mixed solution, and then adding a crosslinking agent and an initiator to the mixed solution, and mixing them evenly to obtain a hydrogel precursor solution;

[0009] S2. pouring the hydrogel precursor solution onto the surface of the bonding substrate treated with oxygen plasma, and completing the polymerization reaction by ultraviolet irradiation, thereby achieving strong bonding between the hydrogel and the substrate.

[0010] As a preferred embodiment of the first aspect, the cross-linking agent is N,N'-methylenebisacrylamide (MBAA), and the mass ratio of the cross-linking agent to the acrylamide monomer is (0.0005-0.001):1.

[0011] As a preferred embodiment of the first aspect, the initiator is ammonium persulfate (APS), and the mass ratio of the initiator to the acrylamide monomer is (0.003-0.004):1.

[0012] As a preferred embodiment of the first aspect, the ultraviolet wavelength used in the ultraviolet irradiation is 365 nm, the power is 40-50 W, and the ultraviolet irradiation time is 160-200 min.

[0013] As a preference of the first aspect above, the bonding substrate is metal, glass, polydimethylsiloxane (PDMS), polymethyl methacrylate (PMMA), ceramic or carbon-based material.

[0014] It should be noted that when pouring the hydrogel precursor on the surface of the bonding substrate, a corresponding mold can be set according to the actual hydrogel shape requirements, and a coating method can also be used when pouring to form a layer.

[0015] In a second aspect, the present invention provides a method for strengthening the toughness of trehalose-modified hydrogel by dehydration induction, the steps of which are as follows:

[0016] S1, dissolving 5-25 parts by weight of trehalose (T) and 7 parts by weight of acrylamide (AAm) monomer in water to form 50 parts by weight of a mixed solution, adding a crosslinking agent N,N'-methylenebisacrylamide (MBAA) and an initiator ammonium persulfate (APS) to the mixed solution, and mixing them evenly to obtain a hydrogel precursor solution;

[0017] S2, pouring the hydrogel precursor solution onto the surface of the bonding substrate treated with oxygen plasma, and completing the polymerization reaction by ultraviolet irradiation, thereby achieving strong and tough bonding between the hydrogel and the substrate;

[0018] S3. Place the bonded hydrogel and substrate in an environment of 65-75°C for dehydration treatment, and finally homogenize them in a sealed container to complete dehydration-induced enhancement of the bonding strength.

[0019] In a third aspect, the present invention provides a method for strengthening the toughness of trehalose-modified hydrogel by dehydration induction, the steps of which are as follows:

[0020] S1, dissolving 5-25 parts by weight of trehalose (T) and 7 parts by weight of acrylamide (AAm) monomer in water to form 50 parts by weight of a mixed solution, adding a crosslinking agent N,N'-methylenebisacrylamide (MBAA) and an initiator ammonium persulfate (APS) to the mixed solution, and mixing them evenly to obtain a hydrogel precursor solution;

[0021] S2, subjecting the hydrogel precursor solution to ultraviolet irradiation to complete polymerization reaction, thereby obtaining a hydrogel material;

[0022] S3. The different hydrogel materials to be bonded are placed in an environment of 65-75°C for dehydration treatment, and then the dehydrated different hydrogels are pressurized in a manner of bonding the bonding surfaces, and finally the pressurized bonded hydrogel material assembly is transferred to a sealed container for homogenization to complete the dehydration-induced strengthening of the bonding strength.

[0023] In a fourth aspect, the present invention provides a method for strengthening the toughness of the bond dehydration induced by trehalose-modified hydrogel, the steps of which are as follows:

[0024] S1, dissolving 5-25 parts by weight of trehalose (T) and 7 parts by weight of acrylamide (AAm) monomer in water to form 50 parts by weight of a mixed solution, adding a crosslinking agent N,N'-methylenebisacrylamide (MBAA) and an initiator ammonium persulfate (APS) to the mixed solution, and mixing them evenly to obtain a hydrogel precursor solution;

[0025] S2, subjecting the hydrogel precursor solution to ultraviolet irradiation to complete polymerization reaction, thereby obtaining a hydrogel material;

[0026] S3. The different hydrogel materials to be bonded are pressurized in a bonding surface-to-bond manner, and then the pressurized hydrogel material assembly is placed in an environment of 65-75°C for dehydration treatment, and finally transferred to a sealed container for homogenization to complete the dehydration-induced strengthening of the bonding strength.

[0027] In a fifth aspect, the present invention provides a method for preparing a hydrogel supercapacitor, the steps of which are as follows:

[0028] S1, dissolving 5-25 parts by weight of trehalose (T) and 7 parts by weight of acrylamide (AAm) monomer in water to form 50 parts by weight of a mixed solution, and then adding electrolyte, crosslinking agent N,N'-methylenebisacrylamide (MBAA) and initiator ammonium persulfate (APS) to the mixed solution, and mixing well to obtain a hydrogel precursor solution;

[0029] S2, subjecting the hydrogel precursor solution to ultraviolet irradiation to complete polymerization reaction, thereby obtaining a hydrogel material;

[0030] S3, using the hydrogel material as an electrolyte, attaching electrodes to both sides of the hydrogel material to form a hydrogel supercapacitor, and the bonding surface between the electrode and the hydrogel material is treated with oxygen plasma in advance;

[0031] S4. Place the hydrogel supercapacitor in an environment of 65-75°C for dehydration treatment, and finally homogenize it in a sealed container to obtain a hydrogel supercapacitor with enhanced bonding strength.

[0032] As a preferred embodiment of the second, third, fourth and fifth aspects, the sealed container available for homogenization is a sealed bag, and the homogenization time needs to ensure that the residual water in the sample is evenly distributed through free diffusion, preferably 3 days.

[0033] It should be noted that in the above-mentioned second aspect, third aspect, fourth aspect, and fifth aspect, the selection and proportion of various raw material components in the hydrogel precursor, as well as conditions such as ultraviolet irradiation, can all refer to the technical solution in the first aspect. Compared with the technical solution of the first aspect, the above-mentioned second aspect, third aspect, fourth aspect, and fifth aspect strengthen the bonding strength based on dehydration induction, and they cover two modes of "dehydration first and then bonding" and "bonding first and then dehydration", which can be selected according to actual needs to optimize the bonding performance and long-term stability of the hydrogel. This strengthening technology can not only effectively improve the mechanical properties of the hydrogel, but also ensure that it maintains a long-term and reliable bonding effect in a variety of harsh environments, and is particularly suitable for the actual needs of high-strength and high-stability bonding.

[0034] In summary, the present invention significantly improves the bonding strength and environmental stability of the hydrogel by introducing trehalose. Trehalose can form a strong hydrogen bond network in the hydrogel, making it more firm and stable during the bonding process between the hydrogel and the substrate. Trehalose also gives the hydrogel good biocompatibility and biodegradability, making the bonding method have unique advantages in the biomedical field. In addition, by combining the dehydration process, the present invention further strengthens the bonding performance while also improving the mechanical strength and resistance to environmental changes of the hydrogel. The dehydration-induced bonding strengthening technology can not only flexibly adjust the bonding strength of the hydrogel, but also significantly improve the stability and reliability of the hydrogel under extreme conditions.

[0035] Compared with the prior art, the trehalose-based hydrogel bonding method of the present invention shows significant advantages, not only has high bonding strength, but also shows excellent stability under extreme environments. On the one hand, the introduction of trehalose enables the hydrogel to form a strong hydrogen bond network during the bonding process, and on the other hand, the bonding performance can be flexibly adjusted by controlling the dehydration conditions, so that it can maintain a reliable bonding effect under complex conditions. The method is simple and easy to operate, suitable for a variety of hydrogel systems, and suitable for a variety of substrates. Therefore, the present invention has a wide range of application potential, especially in biomedicine, electronic equipment and other fields with high requirements for bonding strength, and has significant market value. With the development of technology, it is expected that this technology will play an important role in the field of high-performance adhesive materials in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a flow chart of bonding the hydrogel to the substrate in Example 1.

[0037] Figure 2 The interfacial toughness between the hydrogel prepared in Example 1 and the substrate is used to characterize its bonding performance.

[0038] Figure 3 The bonding properties of the hydrogel prepared in Example 2 on different substrates.

[0039] Figure 4 The environmental tolerance test of the hydrogel prepared in Example 3 includes a DSC test and a TG test.

[0040] Figure 5 Schematic diagram of the dehydration-induced hydrogel bonding strengthening method in Example 4 and Example 5 (including two operation modes of “dehydration first and then bonding” and “bonding first and then dehydration”).

[0041] Figure 6 This is the evolution curve of the bonding performance of the "dehydration before bonding" sample prepared in Example 4 as a function of polymer content.

[0042] Figure 7 This is the evolution curve of the bonding performance of the "dehydration before bonding" sample prepared in Example 4 as a function of dehydration time.

[0043] Figure 8 This is the evolution curve of the bonding performance of the "bonding first and then dehydrating" sample prepared in Example 5 as a function of polymer content.

[0044] Fig. 9 This is the evolution curve of the bonding performance of the "bonding first and then dehydrating" sample prepared in Example 5 as a function of dehydration time.

[0045] Fig.10 These are the evolution curves of the bonding performance of the hydrogels prepared in Examples 4 and 5 as a function of dehydration time in the “dehydration first and then bonding” and “bonding first and then dehydration” modes.

[0046] Fig.11 Schematic diagram of the interface of the trehalose-modified polyacrylamide hydrogel prepared in Example 4 and Example 5 in the "dehydration first and then bonding" and "bonding first and then dehydration" modes.

[0047] Fig.12 This is the trehalose-modified polyacrylamide hydrogel supercapacitor prepared in Example 6.

[0048] Fig.13 The comparison of the bonding performance between the hydrogel electrolyte and the electrode material in the hydrogel supercapacitor (device) prepared in Example 6 before and after dehydration, and the evolution curve of the capacitance retention rate with dehydration time. DETAILED DESCRIPTION

[0049] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific implementation mode of the present invention is described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below. The technical features in each embodiment of the present invention can be combined accordingly without conflicting with each other.

[0050] Example 1

[0051] In this embodiment, the strong bonding of polyacrylamide hydrogels modified with trehalose of different concentrations to a substrate includes the following steps:

[0052] (1) Preparation of hydrogel precursor solution: First, 6 different experimental groups were set up, and 0g, 2g, 4g, 6g, 8g, and 10g of trehalose and 2.8g of acrylamide (AAm) were dissolved in an appropriate amount of deionized water, respectively, so that the total mass of the solution was 20g (the mass fraction of trehalose in the 6 experimental groups was 0wt%, 10wt%, 20wt%, 30wt%, 40wt%, and 50wt%, respectively). Then, for each experimental group, 100 μL of N,N'-methylenebisacrylamide (MBAA) solution (concentration of 0.1M, solvent is deionized water) was added as a crosslinker, and 100 μL of ammonium persulfate (APS) solution (concentration of 10wt%, solvent is deionized water) was added as an initiator. After mixing, the mixture was degassed using a centrifuge at a speed of 2000rpm for 3min to obtain a hydrogel precursor solution.

[0053] (2) Pretreatment and strong bonding of the substrate for each experimental group: Before bonding the substrate to the hydrogel, the substrate must undergo appropriate surface treatment, and then the mold with the casting cavity is placed on the substrate to cast the hydrogel. After UV-induced cross-linking and curing, strong bonding is achieved. Then, the mold is removed and a backing film is attached to the surface of the hydrogel (a crack is pre-set on the edge of the bonding surface to prevent the hydrogel from being partially bonded to the substrate) for a peeling experiment. The process is as follows: Figure 1As shown. Referring to this process, this embodiment uses glass as the substrate, and the specific pretreatment and bonding process are as follows: First, the glass substrate is washed with anhydrous ethanol and deionized water in turn, and the washing process is repeated twice to ensure that the surface of the substrate is clean and pollution-free. The washed substrate is air-dried for use. Next, the substrate is treated with oxygen plasma (treatment time is 5 minutes, power is 200W) to introduce hydrophilic groups, enhance the chemical activity of the substrate surface, and enhance the adhesion between the hydrogel and the substrate. Subsequently, the hydrogel precursor solution is added dropwise to the surface of the substrate and irradiated with ultraviolet light (40W 365 nm; UVP XX-15L, the distance between the sample and the bulb is 5cm), the irradiation time is 180 minutes, and the polymerization reaction is completed. Thus, the cross-linking and curing of the hydrogel on the surface of the substrate are promoted by ultraviolet light irradiation, thereby achieving strong and tough bonding between the hydrogel and the substrate. Finally, the substrate samples bonded with hydrogels obtained in the six experimental groups were named PAAm-0T, PAAm-10T, PAAm-20T, PAAm-30T, PAAm-40T, and PAAm-50T (corresponding to trehalose mass fractions of 0wt%, 10wt%, 20wt%, 30wt%, 40wt%, and 50wt%, respectively).

[0054] For the six substrate samples bonded with hydrogel, in order to test the bonding performance between the hydrogel and the substrate, a 90° peeling test (ASTM D2861) was performed by a universal material testing machine (Instron 5965) to measure the interface toughness, and a humidifier was equipped to prevent the hydrogel from losing water during the experiment. It should be noted that unless otherwise specified, the above peeling experiments were tested at a constant peeling rate of 60 mm / min. The specific 90° peeling test process is as follows: First, before the test, a flexible but inextensible PMMA film (thickness of 100 μm) was glued to the upper surface of the hydrogel of the sample through cyanoacrylate glue to ensure that the displacement during peeling is completely due to the crack extension of the bonding interface without the elongation deformation of the hydrogel itself; then a peeling test was performed, and the PMMA film was applied at 90° to the force required to peel the hydrogel from the substrate, and the force / width-displacement curve was recorded. In the present invention, the 20%~90% range of the force / width-displacement curve is defined as the plateau to calculate its interface toughness, and to characterize the bonding performance.

[0055] In this embodiment, the peeling test results of 6 samples PAAm-0T, PAAm-10T, PAAm-20T, PAAm-30T, PAAm-40T and PAAm-50T are as follows: Figure 2 As shown in the figure, it can be seen that with the increase of trehalose content, the bonding strength of the hydrogel is significantly improved, and the interface toughness increases from 10.4 J / m 2 Increased to 361.3 J / m 2, increased to 36 times of the original value. This is because with the increase of trehalose content, the number of hydrogen bonds on the hydrogel-substrate interface and in the hydrogel increased significantly, resulting in more energy dissipated per unit area when the crack tip expanded.

[0056] Example 2

[0057] In this embodiment, the strong bonding of trehalose-modified polyacrylamide hydrogel to different substrates includes the following steps:

[0058] (1) Preparation of hydrogel precursor solution: First, set up two experimental groups, dissolve 0g and 10g trehalose and 2.8g acrylamide (AAm) in appropriate amount of deionized water, respectively, so that the total mass of the solution is 20g (the mass fraction of trehalose in the two experimental groups is 0wt% and 50wt%, respectively). Then, for each experimental group, continue to add 100 μL N,N'-methylenebisacrylamide (MBAA) solution (concentration of 0.1M, solvent is deionized water) as a crosslinker, and add 100 μL ammonium persulfate (APS) solution (concentration of 10wt%, solvent is deionized water) as an initiator. After mixing, use a centrifuge to degas, set the speed to 2000rpm, and the time is 3min to obtain a hydrogel precursor solution.

[0059] (2) Pretreatment and strong bonding of the substrate for each experimental group: In this example, nickel alloy, stainless steel, glass, PDMS, aluminum alloy, PMMA and ceramic were selected as substrates, and the strong bonding of the hydrogel and the substrate was achieved according to the same pretreatment and bonding process as in Example 1. Finally, the substrate samples bonded with hydrogel obtained in the two experimental groups were recorded as PAAm-0T and PAAm-50T (corresponding to trehalose mass fractions of 0wt% and 50wt%, respectively).

[0060] For the two substrate samples bonded with hydrogel, the interface toughness was measured by a 90° peel test (ASTM D2861) using a universal material testing machine (Instron 5965) in the same manner as in Example 1, so as to characterize the bonding performance.

[0061] In this embodiment, the peeling test results of two samples PAAm-0T and PAAm-50T are as follows: Figure 3 As shown in the figure, the bonding performance of polyacrylamide hydrogel PAAm-0T on nickel alloy, stainless steel, glass, PDMS, aluminum alloy, PMMA and ceramic surfaces was poor, while the polyacrylamide hydrogel PAAm-50T modified with trehalose showed excellent bonding performance on the above surfaces, and its interfacial toughness was 252, 407, 361, 384, 350, 297 and 327 J / m, respectively. 2, increased to 30-40 times of the original. This shows that the polyacrylamide hydrogel modified with trehalose has excellent adhesion to a variety of substrates.

[0062] Example 3

[0063] In this embodiment, the environmental tolerance test of trehalose-modified polyacrylamide hydrogel includes the following steps:

[0064] (1) Preparation of hydrogel precursor solution: First, set up two experimental groups, dissolve 0g and 6g of trehalose and 2.8g of acrylamide (AAm) in appropriate amount of deionized water, respectively, so that the total mass of the solution is 20g (the mass fraction of trehalose in the two experimental groups is 0wt% and 30wt%, respectively). Then, for each experimental group, continue to add 100 μL of N,N'-methylenebisacrylamide (MBAA) solution (concentration of 0.1M, solvent is deionized water) as a crosslinker, and add 100 μL of ammonium persulfate (APS) solution (concentration of 10wt%, solvent is deionized water) as an initiator. After mixing, use a centrifuge to degas, set the speed to 2000rpm, and the time is 3min to obtain a hydrogel precursor solution.

[0065] (2) Then, for each experimental group, the hydrogel precursor liquid was poured into the cavity of the acrylic mold. After the pouring was completed, it was covered with a transparent acrylic sheet to seal it and the mold was fixed with clips. The mold was irradiated with ultraviolet light (45W 365nm; UVP XX-15L, the distance between the sample and the bulb was 5cm) for 180min to complete the polymerization reaction and obtain a hydrogel sample. The hydrogel samples obtained in the two experimental groups were recorded as PAAm-0T and PAAm-30T (corresponding to trehalose mass fractions of 0wt% and 30wt%, respectively).

[0066] In order to test the extreme environmental adaptability of trehalose-modified polyacrylamide hydrogel, the thermodynamic properties of the hydrogel samples in two experimental groups were analyzed by combining differential scanning calorimetry (DSC) and thermogravimetric analysis (TG) to characterize their environmental tolerance.

[0067] The DSC results of the hydrogel samples in the two experimental groups are as follows: Figure 4 As shown in (a), the polyacrylamide hydrogel only crystallized at around -2.4°C, while the trehalose-modified polyacrylamide hydrogel did not show obvious crystallization areas in the range of 30~-24°C, and the solidification point appeared at around -24.9°C. The TG results of the hydrogel samples of the two experimental groups are shown in Figure 4As shown in (b), the solid line is the change of sample weight over time during heating, and the dotted line is the evolution of sample weight loss rate over time. After the introduction of trehalose, the water loss of trehalose-modified polyacrylamide hydrogel was suppressed compared with polyacrylamide hydrogel, and the water loss rate was significantly slowed down. This shows that after trehalose modification, the environmental adaptability of polyacrylamide hydrogel is significantly enhanced.

[0068] Example 4

[0069] In some application scenarios, hydrogels of different shapes or different properties need to be bonded to each other to form a combination for application. In this embodiment, in order to achieve strong and tough bonding of hydrogels in such scenarios, the bonding between hydrogels is strengthened in a "dehydration first and then bonding" mode, such as Figure 5 As shown in (a), the following steps are included:

[0070] (1) Hydrogel preparation and initial mass recording: Hydrogel samples PAAm-0T and PAAm-30T were prepared in the same manner as in Example 3. After the hydrogel was prepared, it was immediately taken out of the mold and weighed as the initial mass of the hydrogel to facilitate subsequent analysis of mass changes during the dehydration process.

[0071] In the hydrogel system, trehalose, as a small molecule that can move freely, cooperates with water molecules and does not participate in the formation of polymer chains. Therefore, trehalose and water are considered as the medium in the hydrogel system. Therefore, according to the preparation settings, the initial medium content of the hydrogel in this example is , initial polymer content Both are 86% and 14%.

[0072] (2) Dehydration treatment: To accelerate the evaporation of water, the hydrogel samples PAAm-0T and PAAm-30T were placed in an oven at 70°C for dehydration. By controlling the dehydration process, the two samples were dehydrated to obtain samples with different medium contents (i.e., the total content of trehalose and water in the hydrogel system) and different dehydration times for subsequent bonding tests. During the dehydration process, the structure of the hydrogel gradually became more compact and the internal water content decreased, thereby improving its mechanical properties and bonding strength.

[0073] (3) Each hydrogel sample after dehydration was bonded and homogenized: two hydrogel samples of the same type after dehydration were taken and closely fitted, and a 5 mm pre-set crack was introduced at the edge of the bonding surface of the hydrogel by setting a small strip of PET film to isolate it (to facilitate the subsequent peeling experiment and control the crack to start expanding at the interface); then a 500 g weight was used to pressurize for 3 minutes, and humidification was maintained throughout the process to prevent excessive loss of water; finally, the sample was placed in a polyethylene sealed bag and homogenized for three days, so that the residual water in the sample was evenly distributed through free diffusion, and finally the bonding strengthening sample in the "dehydration first and then bonding" mode was obtained. In this embodiment, for the two hydrogel samples PAAm-0T and PAAm-30T, hydrogel samples with different medium contents (14%, 19%, 24%, 29%) and different dehydration times (0~48h) need to be prepared respectively, and each needs to prepare a corresponding bonding strengthening sample.

[0074] In order to test the bonding performance between hydrogels in different samples, a 180° peeling test was performed on each bonded reinforced sample using a universal material testing machine (Instron 5965) to measure the interface toughness. The peeling rate was set to 120 mm / min. Except for the peeling angle and peeling rate, the rest of the peeling test operations were the same as the peeling test in Example 1.

[0075] In this embodiment, for hydrogel-hydrogel bonding reinforcement samples with different medium contents, hydrogels with medium contents of 14%, 19%, 24%, and 29% were prepared by a dehydration process in the early stage (the degree of dehydration increased in sequence), and the aforementioned 180° peeling test was performed and the interface toughness was calculated based on the experimental data to characterize its adhesion performance. The results are as follows: Figure 6 As shown in the results, after dehydration, as the polymer content increases, the interfacial toughness of polyacrylamide hydrogel PAAm-0T increases from 5.1 J / m 2 Increased to 26.4 J / m 2 The interfacial toughness of trehalose-modified polyacrylamide hydrogel PAAm-30T increased from 167 J / m 2 Increased to 1743 J / m 2 .

[0076] In this embodiment, for hydrogel-hydrogel bonding samples with different dehydration times, the hydrogel was dehydrated according to the time gradient in the early stage, and the aforementioned 180° peeling test was performed and the interface toughness was calculated based on the experimental data to characterize its adhesion performance. The results are as follows: Figure 7 As the dehydration time increases from 0 to 48 h, the interfacial toughness of polyacrylamide hydrogel PAAm-0T shows a trend of first increasing and then decreasing, reaching a peak of 22.4 J / m at around 3 h.2 The trehalose-modified polyacrylamide hydrogel PAAm-30T decayed to near zero in about 7 hours and remained stable. 2 It continued to increase and then reached a plateau at around 24 hours and remained stable at 1700 J / m 2 nearby.

[0077] The above results show that, regardless of the content scale or time scale, as the degree of dehydration increases, the "dehydration first, then bonding" mode can achieve enhanced bonding performance. In particular, for trehalose-modified polyacrylamide hydrogels, the "dehydration first, then bonding" mode can permanently improve and stabilize bonding performance.

[0078] Example 5

[0079] In some application scenarios, hydrogels of different shapes or different properties need to be bonded to each other to form a combination for application. In this embodiment, in order to achieve strong and tough bonding of hydrogels in such scenarios, the bonding between the hydrogel and the substrate is strengthened in a "bonding first and then dehydrating" mode, such as Figure 5 As shown in (b), the following steps are included:

[0080] (1) Hydrogel preparation and initial mass recording: Hydrogel samples PAAm-0T and PAAm-30T were prepared in the same manner as in Example 3. After the hydrogel was prepared, it was immediately taken out of the mold and weighed as the initial mass of the hydrogel to facilitate subsequent analysis of mass changes during the dehydration process.

[0081] (2) Bonding and pressurizing the hydrogel samples PAAm-0T and PAAm-30T: Two hydrogel samples of the same type were tightly attached, and a 5 mm pre-set crack was introduced at the edge of the bonding surface of the hydrogel by setting a small strip of PET film for isolation; then, a 500 g weight was used to apply pressure for 3 minutes, and during this process, appropriate humidity was maintained to prevent water loss, thereby obtaining a bonded sample. The hydrogel samples PAAm-0T and PAAm-30T were each bonded and used for subsequent dehydration.

[0082] (3) Dehydration and homogenization: After bonding, each bonding sample is dehydrated. Specifically, the hydrogel sample is placed in an oven at 70°C, and the dehydration process is controlled to obtain samples with different medium contents (i.e., the total content of trehalose and water in the hydrogel system) and different dehydration times (0-48h); then, the sample is placed in a polyethylene sealed bag and homogenized for three days to evenly distribute the residual water, and finally the bonding-enhanced sample in the "bonding first and then dehydration" mode is obtained. In this embodiment, for the two hydrogel samples PAAm-0T and PAAm-30T, it is necessary to use the corresponding bonding samples to prepare bonding-enhanced samples with different medium contents (14%, 19%, 24%, 29%) and different dehydration times (0-48h).

[0083] In order to test the bonding performance between hydrogels in different samples, a 180° peeling test was performed on each bonded reinforced sample using a universal material testing machine (Instron 5965) to measure the interface toughness. The peeling rate was set to 120 mm / min. Except for the peeling angle and peeling rate, the rest of the peeling test operations were the same as the peeling test in Example 1.

[0084] In this embodiment, for hydrogel-hydrogel bonding reinforcement samples with different medium contents, hydrogels with polymer contents of 14%, 19%, 24%, and 29% were prepared by a dehydration process in the early stage (the degree of dehydration increased in sequence), and a 180° peeling test was performed and the interface toughness was calculated based on the experimental data to characterize its adhesion performance. The results are as follows: Figure 8 As shown in Figure 2, after dehydration, the interfacial toughness of polyacrylamide hydrogel PAAm-0T increased from 6.2 J / m 2 Increased to 217 J / m 2 The interfacial toughness of trehalose-modified polyacrylamide hydrogel PAAm-30T increased from 163 J / m 2 Increased to 1928 J / m 2 .

[0085] For the hydrogel-hydrogel bonding samples with different dehydration times, the hydrogels were dehydrated according to the time gradient in the early stage, and the peeling experiment was carried out to calculate the interface toughness to characterize its adhesion performance. The results are as follows Fig. 9 As the dehydration time increases from 0 to 48 h, the interfacial toughness of polyacrylamide hydrogel PAAm-0T increases steadily at first and reaches a plateau value of 250 J / m at around 3 h. 2 and lasted for 6 h, then decayed and returned to zero at around 8 h and remained stable. The interfacial toughness of trehalose-modified polyacrylamide hydrogel PAAm-30T first increased from 163 J / m 2It continued to increase and then reached a plateau at around 40 hours and remained stable at 1900 J / m 2 nearby.

[0086] The above results show that, regardless of the content scale or time scale, as the degree of dehydration increases, the "first bonding and then dehydration" mode can achieve enhanced bonding performance. In particular, for trehalose-modified polyacrylamide hydrogels, the "first bonding and then dehydration" mode can permanently improve and stabilize bonding performance.

[0087] In order to compare the differences between the two modes of "dehydration first and then bonding" and "bonding first and then dehydration", the evolution of interface toughness over time in the two modes is plotted in one figure, as shown in Figure 2. Fig.10 As shown in (a) and (b) in the figure. For the failure mode of "bonding first and then dehydrating", when dehydrating is performed after bonding, as the water evaporates, the volume of the hydrogel gradually decreases, the polymer network shrinks accordingly, and some of the hanging chains near the bonding interface will form entanglements in a limited space ( Fig.11 (b) in the figure), thereby enhancing the bonding performance to a certain extent; while in the case of "dehydrating first and then bonding", due to the unevenness of the interface after dehydration, there will be a small gap at the interface after bonding, which will not be affected by entanglement ( Fig.11 (a) in the figure.

[0088] For polyacrylamide hydrogels, the more water is dehydrated within a certain range, the more significant the shrinkage of the polymer network is, and the more likely the hanging chains near the interface are to form entanglements. At this time, the interfacial toughness is dominated by the contribution of entanglements ( Fig.10 (a) in the figure), so the bonding strengthening effect of the "bonding first and then dehydration" mode is better than that of "bonding first and then dehydration"; for the trehalose-modified polyacrylamide hydrogel, during the dehydration process, on the one hand, its network shrinkage is not obvious and it is difficult to form entanglements. On the other hand, the strengthening and repairing effect of trehalose on its network greatly reduces the hanging chains near the interface. Therefore, the influence of the entanglement effect on the bonding performance can be ignored. At this time, the interface toughness is dominated by the bonding under the non-entanglement effect. Therefore, the bonding strengthening effect of the "bonding first and then dehydration" mode is only slightly better than that of "bonding first and then dehydration", and the two are equivalent in terms of values ​​( Fig.10 (b) in the figure.

[0089] In summary, for the trehalose-modified polyacrylamide hydrogel prepared by the present invention, the bonding strengthening effect of the "bonding first and then dehydration" mode is generally better than that of "bonding first and then dehydration".

[0090] Example 6

[0091] In this embodiment, the preparation method of the trehalose-modified polyacrylamide hydrogel supercapacitor comprises the following steps:

[0092] (1) Preparation of electrodes: First, the carbon nanotube paper was pre-cut into 3×2 cm rectangles, and then ultrasonically treated in anhydrous ethanol for 3 min to remove oil and impurities on its surface, and then air-dried for use. Next, one side of the carbon nanotube paper was treated with oxygen plasma (5 min, 200 W), and finally silver nanowires were evenly coated on the other side of the carbon nanotube paper to obtain a carbon nanotube electrode.

[0093] (2) Preparation of hydrogel electrolyte: First, two experimental groups were set up. 0 and 6 g of trehalose and 2.8 g of AAm monomer were dissolved in appropriate amounts of deionized water, respectively, so that the total mass of the solution was 20 g (the mass fraction of trehalose in the two experimental groups was 0 wt% and 30 wt%, respectively). Then, 2 g of LiCl was added to the solution as an electrolyte, 100 μL of MBAA solution (concentration of 0.1 M, solvent was deionized water) was added as a crosslinker, and 100 μL of APS solution (concentration of 10 wt%, solvent was deionized water) was added as an initiator and mixed evenly to obtain a hydrogel precursor solution. Finally, the hydrogel precursor solution was poured into the transparent acrylic mold cavity and sealed, and irradiated with ultraviolet light (40 W 365 nm; UVP XX-15L, the distance between the sample and the bulb was 5 cm) for 180 min to complete the polymerization reaction and obtain a hydrogel sample. The hydrogel samples obtained from the two experimental groups were recorded as PAAm-0T and PAAm-30T (corresponding to trehalose mass fractions of 0wt% and 30wt%, respectively).

[0094] It should be noted that the LiCl electrolyte in the hydrogel precursor solution is added in this embodiment to improve the conductivity of the hydrogel, but it does not affect other mechanical properties of the hydrogel.

[0095] (3) Fabrication of supercapacitors: Two carbon nanotube electrodes were laminated on the two sides of a hydrogel sample (30×20×2 mm), with the plasma-treated side facing inward and the silver nanowire-coated side facing outward. After pressurizing and laminating for 5 seconds, the hydrogel-based supercapacitor was prepared. Fig.12 In the hydrogel-based supercapacitor, the hydrogel is used as an electrolyte, the carbon nanotube paper in the two carbon nanotube electrodes on both sides is the electrode body, and the silver nanowire is used as the current collector.

[0096] (4) After the hydrogel-based supercapacitor is prepared, it can be further dehydrated to strengthen the bonding. In this embodiment, the hydrogel-based supercapacitor is placed in an oven at 70°C for dehydration. By controlling the dehydration process, device samples with different dehydration times and dehydration equilibrium states (mass change within 24 hours is less than 1% of the initial mass) are obtained. Subsequently, the hydrogel-based supercapacitor is placed in a polyethylene sealed bag and homogenized for three days to finally obtain a hydrogel-based supercapacitor after dehydration treatment and in a dehydration equilibrium state.

[0097] In order to characterize the strong interfacial adhesion and environmental adaptability of the assembled flexible energy storage device, this example uses a 180° peeling test to evaluate the interfacial adhesion performance of the trehalose-modified polyacrylamide hydrogel-based device (prepared with PAAm-30T as the electrolyte) before and after dehydration, and a polyacrylamide hydrogel-based device (prepared with PAAm-0T as the electrolyte) is used as a control. In addition, combined with the capacitance test, the evolution of capacitance over time in a dry environment is studied, and the electrical performance of the device is evaluated.

[0098] like Fig.13 As shown in (a), the 180° peeling test results of this embodiment show that in the initial state, after the addition of trehalose, the interface toughness is increased from 27.3 J / m 2 The performance of the trehalose-modified polyacrylamide hydrogel-based device was increased to 267 J / m 2 After dehydration equilibrium treatment, the polyacrylamide hydrogel-based device debonded and the interface toughness was only 4 J / m 2 The interface of the trehalose-modified polyacrylamide hydrogel-based device was strengthened after dehydration, and the interface toughness increased significantly to 1546 J / m 2 about.

[0099] like Fig.13 As shown in (b), the capacitance test results show that the capacitance of the polyacrylamide hydrogel-based device dropped significantly from 100% to 36% within 72 hours. In contrast, the capacitance of the trehalose-modified polyacrylamide hydrogel-based device dropped slightly from 100% to about 80%, a loss of only 20%, demonstrating its excellent environmental adaptability and stable electrical properties.

[0100] The above shows that the trehalose-modified polyacrylamide hydrogel-based flexible energy storage device has excellent mechanical properties, considerable interfacial adhesion properties and good environmental adaptability. It can cope with the challenges of various complex and harsh environments and fully meet the various needs of flexible energy storage equipment.

[0101] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A method for strong bonding of trehalose-modified hydrogels, characterized in that: Here are the steps: S1, dissolving 5 to 25 parts by weight of trehalose and 7 parts by weight of acrylamide monomer in water to form 50 parts by weight of a mixed solution, and then adding a crosslinking agent and an initiator to the mixed solution, and mixing them evenly to obtain a hydrogel precursor solution; S2. pouring the hydrogel precursor solution onto the surface of the bonding substrate treated with oxygen plasma, and completing the polymerization reaction by ultraviolet irradiation, thereby achieving strong bonding between the hydrogel and the substrate.

2. The method for strong bonding of trehalose-modified hydrogels according to claim 1, characterized in that: The cross-linking agent is N,N'-methylenebisacrylamide, and the mass ratio of the cross-linking agent to the acrylamide monomer is (0.0005-0.001):

1.

3. The method for strong bonding of trehalose-modified hydrogels according to claim 1, characterized in that: The initiator is ammonium persulfate, and the mass ratio of the initiator to the acrylamide monomer is (0.003-0.004):

1.

4. The method for strong bonding of trehalose-modified hydrogels according to claim 1, characterized in that: The ultraviolet wavelength used in the ultraviolet irradiation is 365 nm, the power is 40-50 W, and the ultraviolet irradiation time is 160-200 min.

5. The method for strong bonding of trehalose-modified hydrogels according to claim 1, characterized in that: The hydrogel precursor solution is pre-defoamed before casting.

6. The method for strong bonding of trehalose-modified hydrogels according to claim 1, characterized in that: The bonding substrate is metal, glass, polydimethylsiloxane, polymethyl methacrylate, ceramic or carbon-based material.

7. A method for strengthening the toughness of trehalose-modified hydrogel by dehydration induction, characterized in that: Here are the steps: S1, dissolving 5-25 parts by weight of trehalose and 7 parts by weight of acrylamide monomer in water to form 50 parts by weight of a mixed solution, and then adding a crosslinking agent N,N'-methylenebisacrylamide and an initiator ammonium persulfate to the mixed solution, and mixing them evenly to obtain a hydrogel precursor solution; S2, pouring the hydrogel precursor solution onto the surface of the bonding substrate treated with oxygen plasma, and completing the polymerization reaction by ultraviolet irradiation, thereby achieving strong and tough bonding between the hydrogel and the substrate; S3. Place the bonded hydrogel and substrate in an environment of 65-75°C for dehydration treatment, and finally homogenize them in a sealed container to complete dehydration-induced enhancement of the bonding strength.

8. A method for strengthening the toughness of the bond dehydration induced by trehalose-modified hydrogel, characterized in that: Here are the steps: S1, dissolving 5-25 parts by weight of trehalose and 7 parts by weight of acrylamide monomer in water to form 50 parts by weight of a mixed solution, and then adding a crosslinking agent N,N'-methylenebisacrylamide and an initiator ammonium persulfate to the mixed solution, and mixing them evenly to obtain a hydrogel precursor solution; S2, subjecting the hydrogel precursor solution to ultraviolet irradiation to complete polymerization reaction, thereby obtaining a hydrogel material; S3. The different hydrogel materials to be bonded are placed in an environment of 65-75°C for dehydration treatment, and then the dehydrated different hydrogels are pressurized in a manner of bonding the bonding surfaces, and finally the pressurized bonded hydrogel material assembly is transferred to a sealed container for homogenization to complete the dehydration-induced strengthening of the bonding strength.

9. A method for strengthening the toughness of trehalose-modified hydrogel by dehydration induction, characterized in that: Here are the steps: S1, dissolving 5-25 parts by weight of trehalose and 7 parts by weight of acrylamide monomer in water to form 50 parts by weight of a mixed solution, and then adding a crosslinking agent N,N'-methylenebisacrylamide and an initiator ammonium persulfate to the mixed solution, and mixing them evenly to obtain a hydrogel precursor solution; S2, subjecting the hydrogel precursor solution to ultraviolet irradiation to complete polymerization reaction, thereby obtaining a hydrogel material; S3. The different hydrogel materials to be bonded are pressurized in a bonding surface-to-bond manner, and then the pressurized hydrogel material assembly is placed in an environment of 65-75°C for dehydration treatment, and finally transferred to a sealed container for homogenization to complete the dehydration-induced strengthening of the bonding strength.

10. A method for preparing a hydrogel supercapacitor, characterized in that: Here are the steps: S1, dissolving 5-25 parts by weight of trehalose and 7 parts by weight of acrylamide monomer in water to form 50 parts by weight of a mixed solution, and then adding electrolyte, cross-linking agent N,N'-methylenebisacrylamide and initiator ammonium persulfate to the mixed solution, and mixing well to obtain a hydrogel precursor solution; S2, subjecting the hydrogel precursor solution to ultraviolet irradiation to complete polymerization reaction, thereby obtaining a hydrogel material; S3, using the hydrogel material as an electrolyte, attaching electrodes to both sides of the hydrogel material to form a hydrogel supercapacitor, and the bonding surface between the electrode and the hydrogel material is treated with oxygen plasma in advance; S4. Place the hydrogel supercapacitor in an environment of 65-75°C for dehydration treatment, and finally homogenize it in a sealed container to obtain a hydrogel supercapacitor with enhanced bonding strength.

Citation Information

Patent Citations

  • Saccharide composite polyacrylamide hydrogel as well as preparation method and application thereof

    CN110615899A

  • Bio-based ionic gel as well as preparation method and application thereof

    CN114015077A

  • Trehalose modified photo-thermal hydrogel as well as preparation method and application thereof

    CN116535565A

  • Tough anti-fatigue hydrogel for buffering impact and preparation method thereof

    CN118515802A

  • Thin highly absorbable composite material excellent in dry feeling and its manufacturing method

    JP2008119860A